Stereoselective Synthesis of Orthogonally Protected 1,2-Diaminoinositols from D-Mannose - Acurcio, Rita C. (2017)
We present herein a promising novel strategy for the transformation of sugar aldehydes into 1,2-diaminoinositols. This process, based on the sequential intermolecular aza-Henry reaction and intermolecular Henry reaction allowed the total synthesis of a 1,2-diaminoinositols with total stereochemical control. The new route constitutes a simpler and more efficient approach than those previously described routes to 1,2-diaminoinositols and it has the additional advantage of offering the possibility of orthogonal protection of the amino groups.